RECOVERY OF THE ACHILLES TENDON RUPTURE BY MEANS OF HYDROKINETOTHERAPEUTIC METHODS – CASE PRESENTATION (Fiep Bulletin - online, 2014)
We believe that the recovery using the great facilities offered by the aquatic environment and by the various and attractive methods of hydrokinetotherapy is, in many situations, a support which should not be ignored by the  kinetotherapists. We believe that combining the specific kinetotherapy methods is much more efficient than using some isolated methods, and it is an alternative for the recovery based on the principle of individual treatment, knowing that the patients existed first and then the diseases. The objective of theresearch is to draft a recovery programme for Achilles tendon rupture using methods specific to  hydrokinetotherapy and swimming. We supposed that by applying certain exercise systems, specific to therapeutic swimming and hydrokinetotherapy for the recovery following the Achilles tendon rupture, the recovery will be optimum. The information gathered during this experiment is a starting point in drafting the scientific foundation of the physical deficiency recovery concept using hydrokinetotherapy and especially therapeutic swimming.
Keywords: therapeutic swimming; hydrokinetotherapy; Achilles tendon rupture